Compensation, Work Discipline and Work Motivation Relationship to Employee Job Satisfaction - Imam Abrori; Nuril Hidayati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to determine: (1) the influence of the compensation variable on job satisfaction (2) the influence of the variable work discipline on job satisfaction (3) about the effect of work motivation on employee job satisfaction at PT. PP Perkebunan Jember Widodaren . This research is a causal associative study using a quantitative approach. The population in this study were employees of PT. PP Perkebunan Jember Widodaren amounting to 69 people. The sampling technique in this research is census. Data were collected using a questionnaire that had been tested for linearity, multicolonierity and heteroscedasticity tests. The data analysis technique used is multiple regression. The results of this research are at the significant level 5% indicates that: (1) Compensation has a positive and significant effect on employee job satisfaction. This is evidenced by the beta coefficient (β) 0.227 (p <0.05; p = 0.042) and the effect of compensation on employee job satisfaction with a significant level of 0.003 (2) Work motivation has a positive but not significant effect on employee job satisfaction as evidenced by the level of significance of 0.394